Tingkat Kelelahan Pekerja pada Masa Pandemi Covid-19 di Proyek Pembangunan Ruas Jalan Tol Serpong-Cinere - Adinda Kania Prameswari; Dyah Utari; Fathinah Ranggauni Hardy; Azizah Musliha Fitri (Jurnal Kesehatan Komunitas, 2022)
The construction service sector is one of the sectors that has a high risk of both work accidents and occupational diseases, especially during the current Covid-19 pandemic. The implementation of development activities are still carried out by implementing the Covid-19 prevention protocol. The purpose of this study was to determine the relationship between internal factors (age, nutritional status, and work period) and external factors (length of work and workload) with work fatigue to workers in the Serpong-Cinere Toll Road Development Project. This study used a quantitative analytical method with cross sectional design. The population of this study were 100 workers and sampling in this study using total sampling technique. Chi square test results obtained age was variable with p value 0.031 (p <0.05), workload with p value 0.001 (p <0.05), length of work with p value 0.001 (p <0.05), nutritional status with p value 0.964 (p> 0.05) and working period with p value 0.471 (p> 0.05). The conclusion is that age, workload and length of work are related to work fatigue. Nutritional status and period of work were not related to work fatigue. Suggestion for companies is to evaluate working hours and provide appropriate rest areas in the project area.